STATUE OF UNITY TO POLITICAL SYMBOLISM: PATEL’S TRANSITION ROLE FROM FREEDOM FIGHTER TO NATION-FOUNDING FATHER (1928-1948) - Sukhdev Byadwal (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
In the 20th century, what made Sardar Patel a unique part of the freedom struggle compared to other nation builders and after the freedom struggle, in the foundation members' sardar’s role can be viewed as a man like an iron pillar or like Germany’s Bismarck in unification with strict action for the need of the nation and its People. In my paper, I explore my arguments regarding the political environment of that time and Sardar’s vision, a long-term vision for modern India. Sardar's main role can be seen as a Gandhian follower and a struggler for the masses, like the Kheda 1918, Bardoli Satyagraha 1928, mainly an active role in the civil disobedience movement 1930-31 and the Quit India movement 1942. Founding member of the civil services of India, like IAS, IPS, with a modern governance structure for a newly formed nation. The main role can be viewed as a member of the constitutional committees, complete focus on human rights, gender equality, and minority rights. Adoption of the Gandhian way of life in constitutional making. Some said to him as a right-wing Heart in Congress circle on many issues. Patel's main achievement was doing work for the Political unification of this nation.